The Role of Protective Factors in the Predictive Accuracy of the Structured Assessment of Violence Risk in Youth (SAVRY) - Soderstrom, Melanie F. P. (Youth violence and juvenile justice, 2020)
The use of risk assessment instruments has become standard procedure in the juvenile justice system. Most empirical assessments of the predictive validity of these instruments concentrate on the ability of a total risk score, individual risk factors, or risk domains to predict negative juvenile outcomes but fail to consider the utility of the protective factors in influencing or moderating those risks. This study utilizes the Structured Assessment of Violence Risk in Youth to analyze the impact of protective factors on reoffending using a sample (n = 460) of postadjudication juveniles in a southern state. The overall protective domain and two specific protective factors were related to reoffending in bivariate analyses. However, protective factors did not predict reoffending when controlling for risk domains. Rather, further analyses suggest that certain protective factors buffer the effects of some of the risk domains.